Certified Ethical Hacker (CEH) Exam Cram - Easttom, William (Pearson IT Certification, 2022)
CEH v11 Certified Ethical Hacker Exam Cram is the perfect study guide to help you score higher on the updated EC-Council CEH v11 exam. Using the proven Exam Cram method of study, it offers comprehensive foundational learning for all facets of ethical hacking and penetration testing. Chuck Easttoms expert real-world approach reflects both his expertise as one of the leading cybersecurity practitioners and instructors in the world, as well as test-taking insights he has gained from teaching CEH preparation courses worldwide, including courses taught directly for EC-Council. Easttom assumes no prior knowledge: readers will little or no experience in ethical hacking and penetration testing can obtain the knowledge they need to take and pass the exam. He thoroughly covers every CEH v11 topic, including: Reconnaissance and scanning Enumeration and vulnerability scanning System and session hacking Malware, sniffing, social engineering, and DOS attacks Evading security measures Hacking web servers, applications, wireless, mobile, IoT, and OT Cloud computing, cryptography, and more Extensive preparation tools include topic overviews, exam alerts, CramSavers, CramQuizzes, chapter-ending review questions, author notes and tips, and an extensive glossary. The handy Cram Sheet tear-out brings together tips, acronyms, and memory joggers not available anywhere else -- perfect for last-minute study. Powerful Pearson Test Prep practice test software offers an extensive collection of exam-realistic practice questions, with many customization and reporting features: test yourself in study mode, practice exam mode, or flash card mode. The companion website also provides access to several digital assets including the Glossary and Cram Sheet.